Agreed definitions and a shared vision for new standards in stroke recovery research: The Stroke Recovery and Rehabilitation Roundtable taskforce. Issue 5 (July 2017) - Bernhardt, Julie; Hayward, Kathryn S; Kwakkel, Gert; Ward, Nick S; Wolf, Steven L; Borschmann, Karen; Krakauer, John W; Boyd, Lara A; Carmichael, S Thomas; Corbett, Dale; Cramer, Steven C
The first Stroke Recovery and Rehabilitation Roundtable established a game changing set of new standards for stroke recovery research. Common language and definitions were required to develop an agreed framework spanning the four working groups: translation of basic science, biomarkers of stroke recovery, measurement in clinical trials and intervention development and reporting. This paper outlines the working definitions established by our group and an agreed vision for accelerating progress in stroke recovery research.